RU.521 protects against neutrophil extracellular traps-induced vascular endothelial injury by inhibiting cGAS/STING pathway (Bangladesh Journal of Pharmacology, 2024)
This study aims to investigate the effect of RU.521 on improving vascular endothelial injury in 14 acute lung injury patients. Serum myeloperoxidase, double-stranded DNA (dsDNA), IFN-β, and TNF-α levels of patients were detected by ELISA. Neutrophil extracellular traps were used to stimulate human venous endothelial cells (HUVEC). cGAS/STING pathway protein was detected by western blot. The protective effect of RU.521 on HUVEC was evaluated by CCK-8. The effects of RU.521 on cGAS/STING pathway expression were detected by PCR and western blot. The levels of myeloperoxidase and (dsDNA) in acute lung injury patients were significantly increased (p